Strengths and Limitations of Conventional Approaches to the Risk Assessment and Management of EMF Exposure From 5G and B5G Networks - Mazar, Haim; Ball, David J. (Frontiers in Communications and Networks, 2021)
This article describes the current science-based approach to ensuring public safety from RF- EMF base stations. It also acknowledges that a degree of public concern persists, sometimes resulting in violent action, despite that fact that dose limits are seldom if ever approached in practice. One plausible contributor to the wider discord is that whereas there has been a tendency within parts of academia and by some planning authorities to pursue a technocratic policy approach wherein public concerns are attributed to scientific uncertainty around alleged health risks, the reality is that societal concerns over base station siting are broader. Thus, the potential mis-framing of the debate as a purely scientific issue led to inappropriate risk communication exercises which in fact polarised the situation and charged the situation by disenfranchising other potentially legitimate siting concerns. It is recommended that more attention should be paid to the non-health related siting issues, which should be handled by a thoughtful democratic / deliberative process, and that this should not be conflated with the scientific debate over the uncertain and possibly non-existent risks posed by RF EMF complying with existing dose limits. IEEE 95.1 and ICNIRP 2020 standards represent the science-based approach.